HUBUNGAN HASIL UJI SARING DARAH PADA DONOR SUKARELA DAN PENGGANTI DI RSUD ROKAN HULU - Erawati, Erawati; Syukriadi, Syukriadi (IAIN Batusangkar, 2019)
Blood transfusion is to enter blood from the donor to the recipient's circulatory system. During blood transfusions, the presence of blood that is safe from infectious diseases transmitted through blood transfusion. To ensure the safety of the blood, the UTD RSUD Rokan Hulu conducted screening tests on each donor blood with HBsAg test, anti HCV, anti TP and anti HIV. The purpose of this study was to determine the relationship between blood filter test results on voluntary donors with substitute donors in UTD RSUD Rokan Hulu in 2017. The type of this research is descriptive with a retrospective design, conducted in UTD RSUD Rokan Hulu with a population of all donors donating blood from 1 January 2017 to 31 December 2017. Univariate data were processed and analyzed which were presented in table form and bivariate data analysis was processed statistically using Chi Square test. The results showed that HBsAg was reactive at 7 voluntary donors of blood bags (1.4%) and in donors substituting 38 blood bags (1.8%). Anti HCV reactive in voluntary donors 0 blood bags (0%) and in donors substituting 0 blood bags (0%). Reactive anti-TP in voluntary donors of 10 blood bags (2.0%) and in donors substituting 35 blood bags (1.6%). Anti HIV reactive in voluntary donors 3 blood bags (0.6%) and in donors substituting 3 blood bags (0.1%). The Chi square test results showed that there was no correlation between the results of the blood screening tests at voluntary donors and substitute donors.